An experimental study on performance of diesel engine operating with waste tire and waste plastic derived fuel - Mohd. Herzwan, Hamzah (2015)
This thesis presents the experimental study on the performance of single cylinder diesel engine operating with tire derived fuel (TDF), TDF-diesel fuel blends and also plastic derived fuel (PDF). The objectives of this project is to determine the fuel properties of TDF, TDF-diesel fuel blends and PDF, evaluating the performance of TDF and PDF when used in diesel engine and also to investigate the effect when several blend ratios between TDF and diesel fuel are used. The performance testing is conducted using a single cylinder engine test rig operating with variable engine speed and constant load exerted to the engine. The diesel engine is equipped with hydraulic dynamometer and necessary sensors to collect and measure the desired data. The parameters that were measured during testing include engine torque, power, combustion pressure and exhaust emissions. The obtained data for all tested fuels are compared to diesel fuel performance data. Then, the properties of all tested fuels are also determined. Six samples of tested fuels are prepared where TDF is blended with diesel fuel at three different ratios which is 10%, 30% and 50% together with 100% unblended TDF, PDF and diesel fuel. The PDF that used is 100% not blended with any other fuel. The comparison between TDF, TDF-diesel fuel blends and diesel fuel shows that TDF-diesel fuel blends produce higher power and torque compared to TDF and diesel fuel. Among tested blend ratio, TDF10% yield highest power and torque compared to other tested fuel. When the TDF blend ratio increases, the power and torque decreases. For cylinder pressure, TDF50% produce highest peak pressure compared to other tested fuels. When the TDF blend ratio decrease, the peak pressure will decrease. For emission, diesel fuel produce lowest COx and NOx emission level compared to other tested fuels while TDF10% produce closest emission level to diesel fuel. PDF produce lowest power, torque and peak pressure compared to TDF and diesel fuel. PDF also produce lowest NOx and CO emission level compared to TDF and diesel fuel. From the results that were obtained in the experiment, it is concluded that TDF and PDF can be used in diesel engine. However, TDF is not suitable for high speed application since it will cause backfires. Blending process between TDF and diesel fuel enhance the properties of TDF thus producing better performance. From the results obtained, TDF10% produced most optimum performance output compared to the other test fuels.